8(x+2)-4x+7 = 0

8x+16-4x+7 = 0

4x+23 = 0

x = -23/4

8x+16-4x+7 = 0

4x+23 = 0

x = -23/4

8(x+2)-4x+7 = 0

8x+16-4x+7 = 0

4x+23 = 0

x = -23/4

8x+16-4x+7 = 0

4x+23 = 0

x = -23/4

8(x+2)-4x+7=8x+16-4x+7

=4x+23

x=-23/4.

=4x+23

x=-23/4.

Please simplify x^2+8x+7

I am taking it from your statement.

8x+16-4x+7=0

4x+23=0

4x=-23

x=-23/4

8x+16-4x+7=0

4x+23=0

4x=-23

x=-23/4

Simply by factorisation

X^2+7x+x+7= x(x+7)+1(x+7)= (x+1)(x+7)

putting this equal to zero we get solution for x as -1 or -7 ( if you are asked to solve it further asa quadratic equation)

X^2+7x+x+7= x(x+7)+1(x+7)= (x+1)(x+7)

putting this equal to zero we get solution for x as -1 or -7 ( if you are asked to solve it further asa quadratic equation)

8(x+2)-4x+7 = 0, i.e 8x+ 10-4x +7 = 8x-4x = -17, ie. 4x = 17, then x = 17/4 = 4.25

Didn't find the answer you were looking for?